Seeing in my way or your way: impact of intelligence, attention, and empathy on brain reactivity - Montandon, Marie-Louise; Rodriguez, Cristelle; Herrmann, François R.; Eytan, Ariel; Pegna, Alan J.; Haller, Sven; Giannakopoulos, Panteleimon (Frontiers in Human Neuroscience, 2023)
Previous studies showed that neurotypical adults are able to engage in unconscious analyses of others' mental states in the context of automatic perspective taking and experience systematic difficulties when judging the conflicts between their own (Self) and another's (Other) perspective. Several functional MRI (fMRI) studies reported widespread activation of mentalizing, salience and executive networks when adopting the Other compared to Self perspective. This study aims to explore whether cognitive and emotional parameters impact on brain reactivity in dot perspective task (dPT). We provide here an fMRI analysis based on individual z-scores in eighty-two healthy adults who underwent the Samson's dPT after detailed assessment of fluid intelligence, attention, levels of alexithymia and social cognition abilities. Univariate regression models were used to explore the association between brain activation patterns and psychological variables. There was a strong positive association between Wechsler Adult Intelligence Scale (WAIS) and fMRI z-scores in Self perspective. When the Other perspective is taken, Continuous Performance Test (CPT)-II parameters were negatively associated with fMRI z-scores. Individuals with higher Toronto Alexithymia scale (TAS) score and lower scores in mini-Social cognition and Emotional Assessment (SEA) displayed significantly higher egocentric interference-related fMRI z-scores. Our data demonstrate that brain activation when focusing on our own perspective depends on the levels of fluid intelligence. Decreased attentional recruitment and decreased inhibitory control affects the brain efforts to adopt the Other perspective. Egocentric interference-associated brain fMRI activation was less marked in cases with better empathy abilities but the opposite was true for persons who experience increased difficulties in the recognition of emotions.